Effects of Tai Chi on insomnia in elderly people with chronic non-specific low back pain: A study protocol for a randomized controlled trial - Zhang, Feng; Zhang, Boran; Wang, Xiaotong; Huang, Chang; Hu, Boyi (Frontiers in Psychology, 2023)
Introduction Chronic non-specific low back pain (CNLBP) is a complex condition characterized by pain, dysfunction, disturbed sleep, anxiety, and depression, all of which impair the quality of life. Previous studies showed that practicing Tai Chi had effects on chronic low back pain. However, there is a lack of evidence on its impact on sleep. The trial will evaluate the use of Tai Chi as a treatment for insomnia in elderly people with CNLBP. Methods The study design will be a randomized, controlled, open-label trial. Participants (n = 106) will be recruited from the Hospital of Chengdu University of Traditional Chinese Medicine, Qing Yang District University for the Elderly, and Ci Tang Street Community. Participants will be randomly assigned to the Tai Chi group (n = 53) and the control group (n = 53). The Tai Chi group will undergo a Yang-style 24-form Tai Chi program for 8 weeks. The control group will have a waiting period of 8 weeks, followed by 8 weeks of Tai Chi practice. The primary outcomes of this study will be changes in sleep quality and pain intensity. Secondary outcomes of interest will include changes in the quality of pain, range of motion, physical performance, social support, and overall quality of life. Any adverse events and attendance rates will also be reported in this study. Clinical trial registration ChiCTR2200064977.